Automated measurement of single-phase matrix converter test-rig / Adizul Ahmad, Mohd Faizul Md Idros and Abdul Hadi Abdul Razak - Ahmad, Adizul; Md Idros, Mohd Faizul; Abdul Razak, Abdul Hadi (2013)
Power electronics is involved with many parameters and all of these parameters use many test points and equipments in the system. Because of this, the system becomes complicated with many connections of cables between various equipments. It takes a large portion of time connecting the standard hardwired instrumentation, which allows to measure voltage, current and real power. Human monitoring each of the parameters are also not possible. Therefore, this work proposes an interfacing system using Laboratory Virtual Instrumentation Workbench (LabVIEW) programming between test rig and laptop computer. LabVIEW is a platform and development environment for a visual programming language from National Instruments (NI). It is reflected on how to measure variables such as voltage and current by interfacing system through instruments. An installation of NI LabVIEW 8.5 software and Tektronix Mixed Signal Oscilloscope (MSO4054) to the laptop computer is needed as the main procedure. Universal Serial Bus (USB) is used to interface the connection between oscilloscope and laptop computer. Data is measured from Single Phase Matrix Converter (SPMC) circuit and it is generated and displayed by oscilloscope. Through the oscilloscope, measured variables are acquired and were converted into digital formats and transferred it into the laptop computer. Oscilloscope performs the actual measurements.